2012
DOI: 10.4269/ajtmh.2012.11-0386
|View full text |Cite
|
Sign up to set email alerts
|

Development of Leishmania (Leishmania) infantum chagasi in Its Natural Sandfly Vector Lutzomyia longipalpis

Abstract: Abstract. We analyzed the development of Leishmania (Leishmania) infantum chagasi in its natural sandfly vector Lutzomyia longipalpis. In addition, we compared sandfly infections initiated with axenic amastigotes or promastigotes. Our data showed no important difference between Lu. longipalpis infection rates resulting from either type of infections. Furthermore, development of infection was equivalent in both cases. All promastigote forms were found inside the sandfly and, after blood digestion, most of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Accordingly, our experiments with L. donovani showed similar numbers of metacyclic forms in mature infections as well as comparable transmission efficiency in amastigote- and promastigote-initiated P. argentipes infections. Different results were reported with late stage infections of L. infantum chagasi in L. longipalpis (Freitas et al 2012). Here metacyclics were 10 times less represented in amastigote-initiated infections compare to promastigote-initiated infection.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Accordingly, our experiments with L. donovani showed similar numbers of metacyclic forms in mature infections as well as comparable transmission efficiency in amastigote- and promastigote-initiated P. argentipes infections. Different results were reported with late stage infections of L. infantum chagasi in L. longipalpis (Freitas et al 2012). Here metacyclics were 10 times less represented in amastigote-initiated infections compare to promastigote-initiated infection.…”
Section: Discussionmentioning
confidence: 84%
“…Direct comparisons between these two methods are scarce and effects of this factor on transmission potential have not been compared. There is only a single similar study on Leishmania infantum–Lutzomyia longipalpis parasite–vector model (Freitas et al 2012) which was, however, performed using axenic amastigotes that may substantially differ from intracellular ones due to the loss of important factors during a long-term in vitro culture (Pescher et al 2011). Here we compared Leishmania donovani infection in its natural vector Phlebotomus argentipes using culture form promastigotes and amastigotes grown ex vivo in bone marrow-derived macrophages (BMM).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we discriminated between infected vectors (vectors with viable parasites in their gut) and uninfected ones. However, infected vectors may have different infectiousness levels [15] , [40] . Thus, although a reduction in the 3.2% most infected hosts will decrease the total number of infected vectors, and consequently, reduce the R 0 , EIR, and morbidity, quantifying the success of such a control strategy necessitates the development of a dynamic model that involves data on the vector population dynamics and the distribution of the their levels of infectiousness.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the number of Leishmania parasites at the initial stages of the sand fly infection is usually very low (e.g., between 1–500), while sand flies with mature infection frequently harbor tens of thousands of parasites [14] , [15] , [16] . Once the infection in the vector gut has been established through this density-independent process, the progression (that may be density-dependent due to intraspecific competition) to mature transmissible infection, is thought to be almost definite [14] , [15] , [16] . Thus, the probability that the j parasites in equation (1) will infect the vector, s ( j ), is given by: …”
Section: Methodsmentioning
confidence: 99%
“…This finding suggests extremely high susceptibility of P. orientalis for L. donovani ; at present, the similar study using amastigotes is underway in our laboratory. Due to technical difficulties similar studies using amastigotes have not been performed yet in P. orientalis , however, in L. longipalpis Freitas et al [33] demonstrated that promastigote-initiated L. infantum infections are fully comparable to amastigote-initiated ones.…”
Section: Discussionmentioning
confidence: 99%